2006
DOI: 10.5194/acpd-6-3709-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing atmospheric transport models for future regional inversions over Europe. Part 1: Mapping the CO<sub>2</sub> atmospheric signals

Abstract: Abstract. The CO2 source and sink distribution across Europe can be estimated in principle through inverse methods by combining CO2 observations and atmospheric transport models. Uncertainties of such estimates are mainly due to insufficient spatiotemporal coverage of CO2 observations and biases of the models. In order to assess the biases related to the use of different models the CO2 concentration field over Europe has been simulated with five different Eulerian atmospheric transport models as part of the EU… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…This is illustrated in Geels et al (2007), with a twofold increase in the spread of model results between marine and continental stations. This implies a model error twice larger at continental stations than at marine sites.…”
Section: Transport Model Errorsmentioning
confidence: 97%
See 2 more Smart Citations
“…This is illustrated in Geels et al (2007), with a twofold increase in the spread of model results between marine and continental stations. This implies a model error twice larger at continental stations than at marine sites.…”
Section: Transport Model Errorsmentioning
confidence: 97%
“…Following Peylin et al, 2005, daily errors are calculated as the standard deviation of actual hourly (or half-hourly) CO 2 measurements, each day between 11:00 and 16:00. The underlying assumption to link this error calculation to the random part of error in transport modeling is that atmospheric transport models tend to be less reliable for sites and days with larger hourly variability (Geels et al, 2007). The resulting annual mean daily error varies between 0.56 ppm at Pallas, up to 2.84 ppm at Cabauw.…”
Section: Data Errors (Sd Test)mentioning
confidence: 99%
See 1 more Smart Citation
“…The intercomparison study revealed the remarkable improvement of the CO 2 concentration simulation by regional models with horizontal resolutions down to 50 km compared to the coarser global models. The conclusions made by Geels et al (2007) impose severe limitations on the usability of continental CO 2 concentration data from short towers and mountain stations in inversions. Moreover one may also add coastal stations to the "difficult sites" list (Riley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The transport deficiencies become especially critical when trying to invert high space/time resolution of fluxes as compared to monthly fluxes on large regions for which data limitation is probably larger (Gurney et al, 2002). A comprehensive validation of different global (TM3, LMDZ) and regional (HANK, DEHM, REMO) offline transport models were done by (Geels et al, 2007) for several European tall towers and mountain stations. The intercomparison study revealed the remarkable improvement of the CO 2 concentration simulation by regional models with horizontal resolutions down to 50 km compared to the coarser global models.…”
Section: Introductionmentioning
confidence: 99%